PELATIHAN PEMBUATAN PUDING SEDOT (PUDOT) JAHE SEBAGAI PENINGKAT IMUNITAS ANAK DISAAT PANDEMIK COVID-19 - Siswi Wulandari; Linda Sri Kusumawati; Huda Rohmawati; Kurnia Novitasari; Yeni Puspita Anggraini (Universitas Majalengka, 2021)
Coronavirus outbreak that attacks the respiratorytract, which is one of the causesadalahdecreased immunity of the body. Decreased immunity of the body with the same symptoms in people infected with coronavirus including cough, flu, fever, and shortness of breath. Providing balanced nutrition is very important for children, as a preventive measure. Increased immunity of the body can be done by consuming drinks from spices, one of which is ginger. Community service is carried out by providing training on 25 housewives (PKK) and conducted in December 2020 – January 2021 in the village of Sukorame Kediri City. The method used is counseling and demostration of making pudding suction (pudot) ginger while paying attention to health protocol. Residents who participated in this training experienced an increase in knowledge and skills. Obtained the results of 84% of skilled citizens in the manufacture of ginger pudot.